2018
DOI: 10.1016/j.compind.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Apple flower detection using deep convolutional networks

Abstract: To optimize fruit production, a portion of the flowers and fruitlets of apple trees must be removed early in the growing season. The proportion to be removed is determined by the bloom intensity, i.e., the number of flowers present in the orchard. Several automated computer vision systems have been proposed to estimate bloom intensity, but their overall performance is still far from satisfactory even in relatively controlled environments. With the goal of devising a technique for flower identification which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 208 publications
(100 citation statements)
references
References 46 publications
(70 reference statements)
0
99
0
1
Order By: Relevance
“…Soft computing approaches have become the de facto approach for agricultural robotics as they have been found to be able to handle dynamic conditions reliably (Y. Huang et al, ). They have been utilised for a wide range of agricultural tasks: harvesting, yield estimation, weed‐spraying, pollination, and crop management (Bargoti & Underwood, a, b; Dias, Tabb, & Medeiros, ; Kurosaki et al, ; Nachtigall, Araujo, & Nachtigall, ; Sa et al, ; Wan, Toudeshki, Tan, & Ehsani, ; Wang, Song, & He, ; Zhang et al, ). Detection of apples (Bargoti & Underwood, b; Dias et al, ; Inthiyaz, Kishore, & Madhav, ; Moallem, Serajoddin, & Pourghassem, ; Prasad et al, ; Puttemans, Vanbrabant, Tits, & Goedemé, ; Soleimani Pour, Chegini, Zarafshan, & Massah, ) and strawberries (Habaragamuwa et al, ; Puttemans et al, ) has shown good results with detection rates up to 90% of the fruit under real‐world orchard conditions.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Soft computing approaches have become the de facto approach for agricultural robotics as they have been found to be able to handle dynamic conditions reliably (Y. Huang et al, ). They have been utilised for a wide range of agricultural tasks: harvesting, yield estimation, weed‐spraying, pollination, and crop management (Bargoti & Underwood, a, b; Dias, Tabb, & Medeiros, ; Kurosaki et al, ; Nachtigall, Araujo, & Nachtigall, ; Sa et al, ; Wan, Toudeshki, Tan, & Ehsani, ; Wang, Song, & He, ; Zhang et al, ). Detection of apples (Bargoti & Underwood, b; Dias et al, ; Inthiyaz, Kishore, & Madhav, ; Moallem, Serajoddin, & Pourghassem, ; Prasad et al, ; Puttemans, Vanbrabant, Tits, & Goedemé, ; Soleimani Pour, Chegini, Zarafshan, & Massah, ) and strawberries (Habaragamuwa et al, ; Puttemans et al, ) has shown good results with detection rates up to 90% of the fruit under real‐world orchard conditions.…”
Section: Related Workmentioning
confidence: 99%
“…They have been utilised for a wide range of agricultural tasks: harvesting, yield estimation, weed-spraying, pollination, and crop management (Bargoti & Underwood, 2017a, 2017bDias, Tabb, & Medeiros, 2018;Kurosaki et al, 2011;Nachtigall, Araujo, & Nachtigall, 2016;Sa et al, 2016;Wan, Toudeshki, Tan, & Ehsani, 2018;Wang, Song, & He, 2017;Zhang et al, 2017). Detection of apples (Bargoti & Underwood, 2017b;Dias et al, 2018;Inthiyaz, Kishore, & Madhav, 2018;Moallem, Serajoddin, & Pourghassem, 2017;Prasad et al, 2018;Puttemans, Vanbrabant, Tits, & Goedemé, 2017;Soleimani Pour, Chegini, Zarafshan, & Massah, 2018) and strawberries (Habaragamuwa et al, 2018;Puttemans et al, 2017) has shown good results with detection rates up to 90% of the fruit under real-world orchard conditions. A kiwifruit detection system using semantic segmentation was able to detect 76.0% of kiwifruit in a real-world orchard (H. A. .…”
Section: Fruit Detectionmentioning
confidence: 99%
“…Soft computing techniques have been utilized for a wide range of harvesting, yield estimation, weed-spraying, pollination, and crop management within orchards (Bargoti & Underwood, 2017a, 2017bDias, Tabb, & Medeiros, 2018;Kurosaki et al, 2011;Nachtigall, Araujo, & Nachtigall, 2016;Sa et al, 2016;Wang, Song, & He, 2017;Wan, Toudeshki, Tan, & Ehsani, 2018;Zhang et al, 2017). Detection of Apples (Bargoti & Underwood, 2017b;Dias et al, 2018;Inthiyaz, Kishore, & Madhav, 2018;Moallem, Serajoddin, & Pourghassem, 2017;Prasad et al, 2018;Puttemans, Vanbrabant, Tits, & Goedemé, 2017;Soleimani Pour, Chegini, Zarafshan, & Massah, 2018) and strawberries (Habaragamuwa et al, 2018;Puttemans et al, 2017) have shown good results with detection rates up to 90% of the fruit under real-world orchard conditions. A kiwifruit detection system using semantic segmentation was able to detect 76.0% of kiwifruit in a real-world orchard (Williams et al, 2018), showing promise for the detection of the flowers under similar conditions.…”
Section: Fruit and Flower Detectionmentioning
confidence: 99%
“…Our previous work in [11] introduced a novel approach for apple flower detection that relies on a fine-tuned Clarifai CNN [18] to classify individual superpixels composing an image. That method highly outperformed color-based approaches, especially in terms of generalization to datasets composed of different flower species and acquired in uncontrolled environments.…”
Section: Related Workmentioning
confidence: 99%